2018
DOI: 10.1055/s-0043-121264
|View full text |Cite
|
Sign up to set email alerts
|

The PCOS Patients differ in Lipid Profile According to their Phenotypes

Abstract: The results of our study showed differences in lipid profile between lean PCOS patients according to their phenotype based on androgens' level. This effect was abandoned by fat tissue mass in non-lean ones. Further studies should be conducted to explore these associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 37 publications
(48 reference statements)
1
9
0
Order By: Relevance
“…Consistent with our findings, the disturbed hormonal profile in PCOS group could lead to hypercholesterolemia and hypertriglyceridemia as proposed by Pan et al [ 23 ] and Spałkowska et al [ 32 ] who suggested that hyperandrogenism is a leading cause of abnormal lipid profile. SLE-treated animals showed a significant reduction in total cholesterol and TGs with equal efficacy compared to metformin treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our findings, the disturbed hormonal profile in PCOS group could lead to hypercholesterolemia and hypertriglyceridemia as proposed by Pan et al [ 23 ] and Spałkowska et al [ 32 ] who suggested that hyperandrogenism is a leading cause of abnormal lipid profile. SLE-treated animals showed a significant reduction in total cholesterol and TGs with equal efficacy compared to metformin treatment.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with this, we found that a high FG‐score was associated with lower SES; however, this association did not remain significant in logistic regression analyses. It is possible that lean women with PCOS represent a separate PCOS phenotype and metabolic risk in lean women with PCOS could be determined primarily by hyperandrogenism . The present study design did not allow us to compare SES in lean women with PCOS with lean controls.…”
Section: Discussionmentioning
confidence: 93%
“…But another researcher who assessed the lipid profile in lean and non-lean PCOS patients, hyperandrogenemia was defined as free androgen index (FAI) ≥5, whose results show higher levels of total cholesterol, high-density lipoprotein cholesterol in lean patients with FAI <5 than in lean patients with FAI ≥ 5. There were no differences in lipid profile between non-lean patients with FAI ≥ 5 and non-lean patients with FAI <5 4 . Another study has also confirmed these results with Ferriman-Gallwey scores(FGS) and triglycerides are significantly higher in PCOS patients 5 .…”
mentioning
confidence: 73%